The Role of Social Media Networks in Promoting a Culture of Tolerance and Combating Extremism from the Perspective of Gulf Cooperation Council Students Studying at Jordanian Universities - Nejadat , Ali (Jordan Journal of Social Sciences, 2023)
This study aimed to identify the role of social media networks in promoting a culture of tolerance and combating extremism from the perspective of Gulf Cooperation Council (GCC) students studying at Jordanian universities. The study is a descriptive survey that relies on the questionnaire as a tool for data collection. The questionnaire was distributed to an available sample of (286) individuals. The study found that most of the sample has social media accounts, and Instagram was the most browsed site. Social media networks play a prominent role in promoting intellectual and cultural tolerance and combating extremism. However, there are challenges that hinder the dissemination of a culture of tolerance and combating extremism on social media networks, such as the spread of rumors and fake news. The cognitive, emotional, and behavioral effects of social media networks have contributed to promoting a culture of tolerance, combating extremism, and rejecting violence, fanaticism, and sectarianism among people. The study also found statistically significant differences between the responses of the study sample regarding the role of social media networks in promoting the culture of tolerance, while there were no statistically significant differences in the responses of the sample regarding the estimation of the role of social media networks in combating extremism, which can be attributed to demographic variables.